The Use of Physostigmine by Toxicologists in Anticholinergic Toxicity - Watkins, Joseph W. (J Med Toxicol, 2014)
The anticholinergic toxidrome is well described and relatively common. Despite controversy, studies have shown that physostigmine is relatively safe and effective in reversing this toxidrome. We would expect toxicologists would be liberal in its use. We retrospectively analyzed data in the Toxicology Investigators Consortium (ToxIC) registry, representing data from medical toxicologists in multiple institutions nationwide, searching for patients who exhibited an anticholinergic toxidrome, determining what treatment(s) they received, and classifying the treatments as physostigmine, benzodiazepines, physostigmine and benzodiazepines, antipsychotics, or no definitive treatment. The causal agents of the toxidrome were as reported by the treating toxicologist. Eight hundred fifteen consecutive patients with anticholinergic toxidromes were analyzed. Benzodiazepines alone were given in 28.7 %, 12.4 % were given physostigmine alone, 8.8 % received both physostigmine and benzodiazepines, 2.7 % were given antipsychotics, and 47.4 % were given no definitive treatment. In patients who received only physostigmine, there was a significant difference in the rate of intubation (1.9 vs. 8.4 %, OR 0.21, 95 % CI 0.05–0.87) versus other treatment groups. Physostigmine was given at varying rates based on causative agent with use in agents with mixed or unknown effects (15.1 %) being significantly lower than those with primarily anticholinergic effects (26.6 %) (p < 0.001). Patients with anticholinergic toxicity were more likely to receive benzodiazepines than physostigmine. Those patients who received only physostigmine had a significantly lower rate of intubation. Physostigmine was more likely to be used with agents exerting primarily anticholinergic toxicity than in those agents with multiple actions.